2009
DOI: 10.1016/s1808-8694(15)30654-6
|View full text |Cite
|
Sign up to set email alerts
|

Myringoplasty in children: retrospective analysis of 35 cases

Abstract: Myringoplasty is a beneficial procedure in the pediatric population in the hands of a skilled and experienced surgeons. If performed properly, it has a good chance of restoring a child's hearing. However, a large study with a long follow up is warranted in order to come to a definitive conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 14 publications
2
14
0
2
Order By: Relevance
“…In the present study, the youngest child was 8 years old with higher anatomical and audiological success rate (92%) and in children aged between 13 and 17 the success rate was 97%. These results are in agreement with the study of al Khtoum 4 where surgery was performed in 12-14 age groups. Final outcome of myringoplasty depends upon many factors and one among them is duration of followup, which varied in different studies from 6 to 12 months.…”
Section: Observations and Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, the youngest child was 8 years old with higher anatomical and audiological success rate (92%) and in children aged between 13 and 17 the success rate was 97%. These results are in agreement with the study of al Khtoum 4 where surgery was performed in 12-14 age groups. Final outcome of myringoplasty depends upon many factors and one among them is duration of followup, which varied in different studies from 6 to 12 months.…”
Section: Observations and Resultssupporting
confidence: 92%
“…13 Few authors 1,14,9,8,2 found no correlation between the age and surgical results; but most of them opine that older the age better are the results. 15,5,6,16,17,3,4,18 Their argument is that smaller perforations would heal spontaneously, upper respiratory tract infections become less common in elderly children, eustachian tube dysfunction resolves with advancing age. 4,18 Hence, surgery in paediatric age should be performed with caution.…”
Section: Observations and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…El tamaño de la perforación es un factor importante en el éxito de la timpanoplastia en niños. Para algunos autores, las perforaciones mayores se asocian con una menor tasa de éxito, probablemente, debido a: una mayor dificultad quirúrgica (6,35), mayor tamaño del injerto y a menudo a un menor remanente timpánico (13), sin embargo para otros el tamaño no es un factor importante en el resultado (8,12,36,37). En el presente estudio el tamaño preoperatorio de la perforación no demostró diferencias estadísticamente significativas en el éxito quirúrgico.…”
Section: Discussionunclassified
“…Varios estudios evalúan el efecto de la edad sobre la tasa de éxito, algunos han reportado un resultado menos exitoso en la población pediátrica (4,5,6), principalmente debido a las características especiales de esta población, como la disfunción y disposición anatómica de la trompa de Eustaquio y la mayor frecuencia de infecciones respiratorias superiores, que influyen en una mayor tasa de re-perforación (7,8,9,10,11). Por lo tanto, todavía hay controversia en cuanto a la edad ideal a la que se debe realizar una timpanoplastia.…”
Section: Introductionunclassified